If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + 6y = -6y Solving 24 + 6y = -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 24 + 6y + 6y = -6y + 6y Combine like terms: 6y + 6y = 12y 24 + 12y = -6y + 6y Combine like terms: -6y + 6y = 0 24 + 12y = 0 Add '-24' to each side of the equation. 24 + -24 + 12y = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 12y = 0 + -24 12y = 0 + -24 Combine like terms: 0 + -24 = -24 12y = -24 Divide each side by '12'. y = -2 Simplifying y = -2
| X+x+5=19 | | 3w+6y+11x+4x-15y+5w= | | -5x+-3x-8=2x+8 | | 9x-17y=15 | | 4w+9x-14y+3w+6x+5y= | | -7-3q=13 | | 3(x+2)=126 | | 16a+18b+4c+4c-4b-4a= | | uover+3=1 | | x^2-6-x= | | (a+b)x^2+8x(a+b)+15(a+b)= | | 17p+11q+p-5q-5p= | | 254y^2-36x^2= | | =3x+2x+90 | | 6+5-3=x | | 7(2c+3)= | | 16m+6n-6m+11n= | | =3x+2x | | 2-(3x+1)=-5x-9 | | -4m^2-a^2= | | 5-2(x-3)=3 | | 4x^2+4y^2+8y=0 | | (x-1)x^2+7x(x-1)+10(x-1)= | | 10(s-9)=-144 | | 7(k-3)=3k-5findk | | x^4+8x^3+6x^2-44x+29=0 | | 40x-1-60+6=0 | | -3y-7=10 | | (5x+3)(2x^2-15x+18)=0 | | 3[x+2]-2[3x-5]=-14 | | (x+1)3=0 | | 3(x+2)-3(2x-1)=40 |